Effect Of Leadership, Motivation And Discipline Of Work On Employee Performance CV. Kiong Ho Surabaya - Akbarrudin Karisma Putra (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to determine how much influence both partially and simultaneously leadership, motivation and work discipline that occur in CV Kiong Ho Surabaya. This research is included in quantitative research, namely the data used in this study in the form of numbers. The sample from this study was CV Kiong Ho Surabaya employees which numbered 35 respondents. Using the disproportionate stratified random sampling model and the collected data were analyzed using multiple linear regression analysis. The independent variables used in this study are leadership, work motivation, work discipline. While the performance of CV Kiong Ho Surabaya employees is the dependent variable. This study uses primary data, namely data collection by distributing questionnaires. The results showed that the results of the F test showed that employee performance was influenced jointly by leadership, work motivation, work discipline. And the results of partial tests, independent variables consisting of leadership, work motivation, work discipline.